Socio- demographic correlates of overweight and obesity among adults in rural Meerut - Kumar, Shailendra; Garg, Sunil Kumar; Singh, Jai Veer; Bhatnagar, Manjula; Chopra, Harivansh; Bajpai, Shailendra Kumar (Indian Journal of Community Health, 2014)
Background: Obesity is most common nutritional disorder in developed countries and is assuming significant dimensions in developing countries. Objectives: To find out the prevalence of overweight and obesity in adults aged 18 years and above and socio-demographic factors affecting overweight and obesity in rural population of Meerut. To suggest measures for prevention of overweight and obesity in adults population of rural Meerut. Material and Methods: In present community based cross sectional study 1382 individuals aged 18 years and above were covered from 400 families spread over 5 villages with the help of systemic random sampling in rural area of Meerut District. The Individuals were interviewed and examined personally using Pre-designed and Pre-tested Questionnaire. Results: Out of 1382 individuals 244 (17.7%) were having BMI ? 25. Prevalence of obesity in females (22%) was found more than males (13.8%). Prevalence of Overweight and Obesity increased with advancing age, maximum being in age group 50-59 years (22.2%). Maximum numbers of males (19.9%) were overweight in their most productive life (30 -39 years) whereas maximum females were overweight in their menopausal decade i.e. 40-49 years (32.8%). Overweight was more in persons who were married (18.9%), professional/Technical person (33.3%), Savarna upper caste (23.1%), belonging to high standard of living index (21.0%), person living in joint families (18.2%), and Alcoholics (18.6%) while smokers were having lower prevalence of overweight (10.6%). Conclusion: The prevalence of Overweight and Obesity is increasing in adult population of rural area. Various socio-demographic correlates are affecting the prevalence of Overweight and Obesity in Rural population.